Environmental Management System Framework for Sustainability Achievement in Higher Educational Institutions - Waqar, A.; Wasim, A.; Salman, H.; Jahanzaib, M.; Aziz, H. (Journal of Advanced Research in Business and Management Studies, 2020)
The purpose of this paper is to map an environmental management system (EMS) framework for higher education institution (HEI) of Pakistan. On the basis of extensive literature review, environmental management system ISO 14001 framework was proposed for HEIs of developing countries. Then Initial environmental review (IER) was conducted through interviews, questionnaire and observations; followed by strength, weaknesses, opportunities and threats (SWOT) analysis to identify key environmental concerns of the selected public sector university. Finally, environmental management system implementation plan was developed for university in the light of ISO 14001 guidelines. Both direct and indirect interactions were considered to scan the current environmental practices of university. The SWOT analysis indicated that university is working somehow satisfactorily in transportation, but there is a need of improvements in resource consumption, landscaping, air quality and purchasing. The environmental management plan for managing all the major and minor concerns have been proposed on the basis of gaps experimented through IER and SWOT analysis. The analyses of quantifiable targets including carbon and water footprints have not been carried out in the plan. Following of EMS guidelines at the university will help to reduce the direct and indirect impacts of different activities on the environment. It will also help to create environmental awareness in young minds that how to integrate sustainability in everyday life. Educational institutions of Pakistan are paying less attention towards the environmental protection. In addition, the awareness of environment protection is also limited. This research is unique in Pakistan in the sense that it will help to explain the procedure for identification of major environmental concerns and mapping environmental management system for a university.